Design of a 4-level active photonics phase change switch using VO 2 and Ge 2 Sb 2 Te 5 - Meng, Yun (2019)
The objective of this work is to design and demonstrate multilevel optical switches by combining different phase change materials. Ge2Sb2Te5 and VO2 nanolayer structures were designed to maximize the optical contrast between four different reflective states. These different optical states arise due to the independent structural phase transitions of VO2 and Ge2Sb2Te5 at different temperatures. The transfer matrix method was used to model Fresnel reflection for each structural phase combination and then to optimize the VO2 and Ge2Sb2Te5 layer thicknesses, which were found to be 70 nm and 50 nm. These multilevel optical switching results provide further possibilities to design composite materials for applications in active and programmable photonics.